PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMPN 1 SIJUNJUNG - Rahayu, Dyah Pramesya (Jurnal Edukasi dan Penelitian Matematika, 2024)
Once a learning process is over, the results are the skills that students have acquired. The results of students' education are significantly impacted by the activities that take place in the classroom. Students in the eighth grade at SMPN 1 Sijunjung continue to have poor mathematical learning outcomes. Applying the PBL model will solve the problem. This research set out to compare the effectiveness of the PBL paradigm with that of direct instruction in mathematics for eighth graders at SMPN 1 Sijunjung. The research methodology that will be employed is known as quasi-experimental research. Class VIII.1 and class VIII.2 at SMPN 1 Sijunjung were selected as the research sample. The two groups of samples were compared for normality, homogeneity, and hypothesis testing using the t-test. At the 5% level of significance, the test findings demonstrated that H0 was rejected with a P-value of 0.002. Students in the PBL group achieved higher test scores in mathematics compared to the control group. Therefore, the PBL method was effective.Keywords : Model Problem Based Learning, Learning Outcomes, Direct Learning Model